2016
DOI: 10.1021/acs.jpca.6b03805
|View full text |Cite
|
Sign up to set email alerts
|

New Insights of the Fenton Reaction Using Glycerol as the Experimental Model. Effect of O2, Inhibition by Mg2+, and Oxidation State of Fe

Abstract: The use of iron ions as catalyst of oxidation with hydrogen peroxide, known as the Fenton reaction, is important for industry and biological systems. It has been widely studied since its discovery in the 19th century, but important aspects of the reaction as which is the oxidant, the role of oxygen, and the oxidation state of Fe still remain unclear. In this work new mechanistic insights of the oxidation of carbohydrates by the Fenton reaction using glycerol as experimental model are described. The reaction wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 45 publications
2
6
0
Order By: Relevance
“…If the iron catalyst residue catalyzes the quenching, then the Fenton oxidation could be a comparable reaction, whereby Fe­(II) and Fe­(III) undergo electron transfer. The kinetics of the Fenton reaction have been extensively studied and the activation energy is ordinarily in the range of 2–50 kJ mol –1 . Our determined value is clearly within this rather broad range, suggesting that it is consistent with (although not unique to) a comparable electron transfer reaction.…”
Section: Results and Discussionsupporting
confidence: 51%
“…If the iron catalyst residue catalyzes the quenching, then the Fenton oxidation could be a comparable reaction, whereby Fe­(II) and Fe­(III) undergo electron transfer. The kinetics of the Fenton reaction have been extensively studied and the activation energy is ordinarily in the range of 2–50 kJ mol –1 . Our determined value is clearly within this rather broad range, suggesting that it is consistent with (although not unique to) a comparable electron transfer reaction.…”
Section: Results and Discussionsupporting
confidence: 51%
“…Anthocyanins are known to remove H 2 O 2 from cells that mainly occurs by the Fenton reaction. It takes place through the hydroxyalkene group of of the anthocyanin structures via the mechanism proposed for this reaction (Vitale et al 2016). Hence, a large part of their bioactivities can be explained by this important function.…”
Section: Introductionmentioning
confidence: 99%
“…Even reactive α-HHs can survive more than a day under certain conditions (e.g., neutral pH, low water content, low temperature). In that case, transition metals in the condensed phase will be a species that can react with peroxides. The key issue is that the mechanisms of the Fenton (Fe 2+ + H 2 O 2 ) and Fenton-like reactions (Fe 2+ + ROOH/ROOR′) are still not fully understood. Recent experiments have revealed that the formation of reactive intermediate species depends on the pH, coreactants, and water content of the reaction medium. , For example, in a water-poor medium, the reaction of Fe 2+ with H 2 O 2 produces oxo–ferryl (Fe IV O 2+ ) species and other products rather than OH radicals. ,, It has been reported that in a dry acetonitrile solution, the Fenton reaction exclusively produces Fe IV O 2+ , while the reaction in the presence of >10% water in the solution produces OH-radicals . Furthermore, the decomposition of methyl hydroperoxide CH 3 OOH and ethyl hydroperoxide C 2 H 5 OOH in the presence of Fe 2+ in water at pH 2 produces corresponding alkoxy radicals RO • , rather than OH-radicals .…”
Section: Atmospheric Implications and Challengesmentioning
confidence: 99%